A study on technophobia among employees at Dewan Bahasa Dan Pustaka (DBP) Kuching, Sarawak/ Athirah Md. Hassim - Md. Hassim, Athirah (2016)
Human used the technology to make work easier and smooth. Interaction with technology sometimes can make the human feeling become uncertainty. The term technophobia was not the current issues especially in the organization among worker. Therefore, this study was conducted to evaluate the technophobia among employees. The purpose of this study was to identify the level of competencies on technology, the behaviour of employees toward the software and hardware and the causes of technophobia among employees in the organization. A study was conducted on Dewan Bahasa dan Pustaka, division Kuching, Sarawak. The subject was office support personnel that work in the organization. Statistical Package for Social Science (SPSS) software version 20.0 used to analysis the data. The result showed that the level of competencies among Dewan Bahasa dan Pustaka employees was positive as well as the behaviour of employees toward the software and hardware and negative in the causes of technophobia but employees still have fear to technology especially to the new technology. In conclusion, some recommendation and suggestions to the future researcher was made.